INVESTIGATING THE EFFICACY OF RSI IN THE NIFTY 50 INDEX - Bansal, Sagar (Digital Repository of Theses - SSBM Geneva, 2023)
This dissertation evaluates the effectiveness of the Relative Strength Index (RSI) in the NIFTY 50 index in the Indian stock market. The study compares RSI's performance to a Buy and Hold strategy using historical data analysis, simulation, and statistical analysis on data from 2000 to 2021. Results show that RSI can identify potential trading opportunities but its success depends on specific settings. 33 RSI strategies were analyzed with positive returns seen when used for buy decisions in divergence scenarios. The RSI outperformed a Buy and Hold strategy in average return, maximum potential, and stability, but the choice of settings such as the period and RSI threshold levels are crucial. The industry's popular RSI(14,30/70) strategy resulted in negative returns. The study has limitations in terms of data and methodology and its results may not be generalizable to other assets. The study highlights the importance of appropriate settings and risk management techniques in using RSI as a trading signal. Future research opportunities include expanding the data set and considering transaction costs.